An historico-juridical consideration of the Jesuit fourth vow: Special obedience to the Pope with regard to missions. - Doiron, Michael J. (University of Ottawa (Canada), 1995)
This dissertation addresses the question: what is the matter of strict juridical obligation incurred by one who professes the fourth vow in the Society of Jesus. Only one "grade" or group of Jesuits profess the Society's "fourth vow" which promises "special obedience to the Sovereign Pontiff with regard to the missions." Since the investigation concerns a vow of obedience, Chapter One considers the emergence of the phenomenon of religious obedience as it was understood and developed through the customs, the rules and the "proper law" of various religious communities which grew in the Church. Chapter Two probes the influences working in the life of the founder, Ignatius of Loyola, the birth of the Spiritual Exercises and the events and documents which led to the establishment of the Society of Jesus. Chapter Three examines The Constitutions of the Society of Jesus, especially those Parts which deal with the two vows of obedience. Specific attention is given to the manner in which the notion of "mission" was understood and carried out by the first Jesuits. Various general principles recognized by the Church which place some limitations on the juridical obligation incurred by one who professes a vow of obedience are also cited. In Chapter Four a review of the historical development of the juridical understanding of the fourth vow is undertaken and then reconsidered in the light of the renewed legal context brought about by the Second Vatican Council and the revision of the Code of Canon Law. The Chapter then looks to the future and suggests possible developments which may occur regarding the evolution and the application of the Jesuit fourth vow. It is the primary conclusion of this study that the fourth vow is to be understood as follows: the vow highlights and focuses the essential missionary end of the Society; it legitimately amplifies the commitment of the third vow with a greater intensity and it extends that commitment with elements of obligation not strictly required by the third vow. The Constitutions specify the matter of juridical obligation over and above that which is legally required by the third vow: a professed Jesuit is not to seek (directly or indirectly) but to accept, immediately and without excuse, missions from the pope even to go to non-Christian countries without requesting provisions for the journey, nor causing a request for anything temporal to be made. It is also concluded that doctrinal matters are not part of the proper object of the fourth vow. The fourth vow, even though it is a special obedience to the pope, does not compromise the ordinary, proper power of the superior general over the institute which he governs. By analogy to canons 332 and 333 which deal with the pope's relationship with bishops, any personal papal mission can be understood to strengthen and safeguard not only the proper, ordinary and immediate power of the superior general, but also the essential nature of the Society itself. (Abstract shortened by UMI.)
Keywords: Theology.